Local engagement with international economic law and human rights - Biukovic, Ljiljana, 1962-; Potter, Pitman B., 1953- (Edward Elgar Publishing, 2017)
International economic law and human rights have been rapidly evolving and expanding in recent decades. This collection grew out of a central objective to explore methods of domestic engagement with international trade and human rights norms, and the inherent difficulties in establishing balanced links between these two international law regimes. It does so by providing an analysis of global regulation and the impact of international organizations on domestic laws. Through conceptual and structural analysis coupled with local analysis and a China-focused case study, this book investigates the socio-legal dimension of the interaction between international economic law and human rights, and particularly the relationships between local arrangements and international legal regulations and rules. The common thread of the chapters in this collection is a focus on the application of socio-legal normative paradigms in building knowledge and policy support for coordinating local performance with international trade and human rights standards in ways that are mutually sustaining. The authors also suggest new approaches to government policies on trade development and human rights protection. The substantive excellence and complexity of the research presented make it an excellent resource for students and scholars of International Law.